An Adaptation Model for Personalized E-Assessments - Saul, Christian; Wuttke, Heinz-Dietrich (International Journal of Emerging Technologies in Learning (iJET), 2013)
Over the last decade, a large number of e-assessment system and tools were developed. However, they all provide assessments that are characterized by a static structure (ordered sequence of questions, predefined start and ending, etc.). This approach does not consider students individual knowledge or characteristics. Instead, each student has to answer the same questions. The work presented in this paper focuses on a personalized e-assessment system (askMe!) that not only identifies, but also supports and even compensates deficits in studentsâ?? individual learning by considering studentsâ?? strengths and preferences. In this paper, the core, the adaptation model of the system is presented that defines what can be adapted, as well as when and how it is to be adapted.